Does Warfare Matter? Severity, Duration, and Outcomes of Civil Wars - Balcells, L; Kalyvas, SN (SAGE Publications, 2014)
Does it matter whether a civil war is fought as a conventional, irregular, or symmetric nonconventional conflict? Put differently, do “technologies of rebellion” impact a war’s severity, duration, or outcome? Our answer is positive. We find that irregular conflicts last significantly longer than all other types of conflict, while conventional ones tend to be more severe in terms of battlefield lethality. Irregular conflicts generate greater civilian victimization and tend to be won by incumbents, while conventional ones are more likely to end in rebel victories. Substantively, these findings help us make sense of how civil wars are changing: they are becoming shorter, deadlier on the battlefield, and more challenging for existing governments—but also more likely to end with some kind of settlement between governments and armed opposition. Theoretically, our findings support the idea of taking into account technologies of rebellion (capturing characteristics of conflicts that tend to be visible mostly at the micro level) when studying macro-level patterns of conflicts such as the severity, duration, and outcomes of civil wars; they also point to the specific contribution of irregular war to both state building and social change.